Impact of Job Involvement on Organizational Effectiveness: A Study Among Faculty Members - Pathak, Ravindra; Patwardhan, Manoj (Prabandhan: Indian Journal of Management, 2011)
As we know that human resources are a vital part of any organization. In fact, there is nothing wrong in saying that human resources are the backbone of any business. Nothing can really match the strength of highly motivated and progressive employees. Human resource is the repository of knowledge and they provide competitive lead to any organization. In this respect, the present study examines the impact of job involvement on organizational effectiveness among the faculty members working at the technical institutes. Job involvement (JI) is the degree to which employees immerse themselves in their job, invest time and energy in them, and view work as a central part of their overall lives. Job involved employees are likely to believe in the work ethic, to exhibit high growth needs, and to enjoy participation in decision making, while Organizational Effectiveness (OE) is the extent to which an organization achieves its goals with the given resources and means. An organization remains effective as long as it uses its resources in an efficient manner and continues to contribute to the large system. The results of this study revealed that job involvement was positively correlated with organizational effectiveness. Finally, the practical implications of this research for organizations are discussed. This research was conducted during the month of Mar-09 to Aug-09.